2006
DOI: 10.1159/000092285
|View full text |Cite
|
Sign up to set email alerts
|

Primary Focal Hyperhidrosis: Disease Characteristics and Functional Impairment

Abstract: Background: There are few published data on the clinical characteristics of hyperhidrosis. Objective: To describe the functional impairment caused by primary focal hyperhidrosis. Methods: Patients with hyperhidrosis (n = 345) were enrolled at the Department of Dermatology, University of Würzburg. Controls (n = 154) were a convenience sample of subjects without hyperhidrosis. Hyperhidrosis characteristics, health-related quality of life and functional impairment were assessed. Results: Patients with axillary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 54 publications
6
121
1
1
Order By: Relevance
“…More than a third (35.18%) of all evaluated patients in this study reported positive family history, which was in agreement with other studies, where it ranged from 30% to 65% (4,7,13).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…More than a third (35.18%) of all evaluated patients in this study reported positive family history, which was in agreement with other studies, where it ranged from 30% to 65% (4,7,13).…”
Section: Resultssupporting
confidence: 93%
“…Various methods for reducing excessive sweating include: special diets (without coffee, tea, coca-cola, chocolate), diverse antiperspirants, such as over-the counter ointments/tinctures, topical aluminium chloride, medicines, drugs (oral anticholinergics), tap water ionophoresis (9), intradermal injections of botulinum toxin type A (botox) (10,11), but only surgical treatment has shown the best long-term results (12)(13)(14).…”
Section: Surgical Techniquementioning
confidence: 99%
“…It is likely that many of these patients meet criteria for SAD as well, because a convenience sample of 354 patients reported moderate to extreme limitations resulting from Hyperhydrosis in meeting people for the first time, being in public places, shaking hands, developing personal relationships, participation in family events, and sexual activities compared to controls. [54] Second is essential tremor, a condition that also can lead to social impairment and fear of being noticed for trembling.…”
Section: Fear Of Showing Anxiety Symptomsmentioning
confidence: 99%
“…In dermatology, health-related quality of life instruments are dominated by the Dermatology Life Quality Index [18], which is used widely [19,20,21]. Other disease-specific quality of life instruments exist and are described elsewhere [22, 23].…”
Section: Outcome Measures In Dermatologymentioning
confidence: 99%